(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The World Health Organization (WHO) since its foundation in 1946 has worked for the improvement of global health and the fight against infectious diseases by bringing out preventive measures to curb the spread of viruses whiles working on approved medicines and vaccines to help heal infected people. The novel Covid-19 pandemic has currently affected almost every country in the world, and it has greatly caused an effect on the global economy at large. Whiles the World Health Organization is bringing out the specific initiative to address this targeted global health problem, many individuals are also relying on traditional methods to immune their systems as well as protect themselves from contracting the Covid-19 virus. Although, the WHO has declared that these traditional remedies are not certified and approved by the organization, the uncertainties and spontaneous reaction of people not to become victims of the Covid-19 virus employs these traditional remedies, although they are not certain about its effectiveness. This study explores the increase demands for ginger as a root crop to help boost the immunity of the body against the Covid-19 virus, as well as reveal the impact of the Covid-19 on the global economic export of ginger in the global market. The increase in the prices and demand of ginger in some countries in the world can fundamentally be credited to two fundamental factors. The first being the effect of the novel Covid-19 pandemic on international ginger trade, whereby there was an increase in the logistics costs since most borders and countries were under lockdown, and workers were self-isolating themselves from contracting the virus which in the long term resulted to the limited supply of goods for export. The second factor is attributed to the hearsay and tittle-tattle in some countries that ginger can be used as a therapeutic for the novel Covid-19 virus. This article has revealed that the Covid-19 pandemic has affected the export of ginger from China. China which happens to the largest international export country to export ginger globally experienced a decrease in the quantity of ginger exportation during the first quarter of 2020. However, the inability of China to export enough ginger has paved way for other countries such as Peru, Indonesia and Germany, Spain, and Turkey to increase in the export of their ginger to other countries. The increase in demand of ginger in this Covid-19 season is attributed to the ideology of consuming such root crop to boost the immune system of people. This paper argues that irrespective of the WHO unapproved use of ginger as a traditional remedy to cure the virus, people are still using this indigenous skill of herbal healing to boost their immune system. This provides reassurance and safety to people’s health. This assurance of the benefits derived from ginger consumption has led to an increase in demand for it, which has also increased in the global economic impact on ginger export.